MEDIA MENGUNGKAP NASAB PARA CALON PRESIDEN TAHUN 2024 : (RELASI NASAB DENGAN POLITIK IDENTITAS) - Lusiawati, Ira; Fitriawati, Diny; Ghassani, Rizqi (JURNAL KEBANGSAAN RI, 2023)
The mass media carried out massive coverage regarding the declaration of the presidential candidates (candidates) for the Republic of Indonesia in 2024. This style of reporting on the presidential candidates not only communicates the achievements that have been achieved for each presidential candidate, but also reveals more about their lineage or lineage. The method used by the media has a big impact on the public in making choices, considering that lineage or lineage gives confidence to the presidential candidates to get support from potential voters. Likewise, prospective voters will get a complete reference regarding the profiles of the presidential candidates they will choose. Moreover, one of the functions of the media, namely, to inform, is very involved in the campaign process for each presidential candidate by reviewing more deeply about various matters including the background on the heroic ethos, and figures of the national Islamic movement. This can be a reinforcement to convince voters, especially from Muslims as the majority voter. Based on these conditions, this study aims to determine the process of disclosing lineage or lineage with respect to general election contestation (election). To explain this, the method used is descriptive qualitative with the type of media content analysis. The findings in this study are the campaign process which presents the symbols of identity politics through lineage to become reinforcement in the course of contestation. Ethnic and religious ancestry that is bound to the presidential candidates, of course as the inclusion of symbols that are part of identity politics.